2011
DOI: 10.1007/s12105-011-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Cadherin Expression and Histopathologic Type, Metastasis, or Patient Outcome in Oropharyngeal Squamous Cell Carcinoma: A Tissue Microarray Study

Abstract: Altered cadherin expression is important for metastasis in many carcinomas including head and neck squamous cell carcinoma (SCC). We evaluated E- and N-cadherin expression specifically in oropharyngeal SCC and correlated this with clinical and pathologic features. Oropharyngeal SCC patients with clinical follow up information were identified from clinician databases from 1996 through 2007 and tissue microarrays created. Tumors had been previously typed histopathologically as keratinizing, non-keratinizing, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
2
18
4
Order By: Relevance
“…Several studies show positive correlation between E-cadherin expression and nodal metastasis (Tanaka et al, 2003;Bosch et al, 2005;Foschini et al, 2008;Foschini et al, 2013) but others including our study, dispute this (Mahomed et al, 2007;Lopes et al, 2009;Mostaan et al, 2011;Ukpo et al, 2012;Rosado et al, 2013). An editorial by Cerezo (2011) DOI:http://dx.doi.org/10.7314/APJCP.2014.15.5.2145 Changed Expression of E-cadherin andGalectin-9 …”
Section: Discussioncontrasting
confidence: 52%
“…Several studies show positive correlation between E-cadherin expression and nodal metastasis (Tanaka et al, 2003;Bosch et al, 2005;Foschini et al, 2008;Foschini et al, 2013) but others including our study, dispute this (Mahomed et al, 2007;Lopes et al, 2009;Mostaan et al, 2011;Ukpo et al, 2012;Rosado et al, 2013). An editorial by Cerezo (2011) DOI:http://dx.doi.org/10.7314/APJCP.2014.15.5.2145 Changed Expression of E-cadherin andGalectin-9 …”
Section: Discussioncontrasting
confidence: 52%
“…A recent TMA study of E-cadherin expression in oropharyngeal squamous cell carcinoma20 failed to show a significant correlation between the expression of E-cadherin and histologic type, nodal and distant metastasis, suggesting that E-cadherin expression may not be a predictor of nodal or distant metastasis in these tumors. The inconsistent results in several studies are limit the use of these markers to predict patient outcome.…”
Section: Discussionmentioning
confidence: 94%
“…These investigations suggested that the probability of complete EMT in OSCC is very low. 9,10 In line with these reports, Pod was used alongside E-and N-Cads to evaluate invasive patterns of OSCC and the results indicated the probability of CCI in these cancers. 3,11 A plethora of molecular pathways and markers is involved in the invasion of cancer cells, however the most popular proteins to define EMT and CCI have been the cadherin family, mesenchymal markers like vimentin and the trans-membrane glycoprotein Pod due to its possible role in CCI.…”
Section: Introductionmentioning
confidence: 86%
“…The latter was classified into 0 where <1% of tumor cells stained positive; 1, if !1-<40% were positive; 2, when !40-<80% showed immunoreactivity and 3 in cases with !80% staining of neoplastic cells. The multiplication of these values was rated as negative (0), weak (1-2), moderate (3-4) and strong (6)(7)(8)(9). Negative and weak tumors were considered E-and N-cadherin negative, while moderate and strong cases were regarded positive for these markers.…”
Section: Analysis Of Immunostained Sectionsmentioning
confidence: 99%